2022
DOI: 10.21272/fmir.6(3).18-25.2022
|View full text |Cite
|
Sign up to set email alerts
|

Does the efficiency of working capital management and environmental, social, and governance performance affect a firm’s value? Evidence from the United States

Abstract: This study evaluates the efficiency of U.S. firms’ working capital management (WCME) by employing the data envelopment analysis technique (DEA). This study uses regression analysis to examine the impact of WCME and environmental, social, and governance (ESGP) performance on U.S. firm value. This study uses a data sample consisting of 964 firm-year observations from a longitudinal panel collected from 2016 to 2019. Endogeneity issues and the employment of additional analyses for robustness were considered. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
49
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 37 publications
13
49
0
Order By: Relevance
“…For instance, current and quick ratios have been embraced to measure firms’ liquidity levels (Shin & Soenen, 1998 ). Therefore, it has been slammed for its inherent static nature (Emery & Cogger, 1982 ; Habib, 2022 ; Habib & Kayani, 2022 ; Habib & Mourad, 2022 ). Alternatively, Richards and Laughlin ( 1980 ) proposed the adoption of cash conversion cycle (CCC), but this was slammed for being mathematically inaccurate, not focusing on funds tied up, and lacking differentiation in the weights appointed to each element of working capital.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, current and quick ratios have been embraced to measure firms’ liquidity levels (Shin & Soenen, 1998 ). Therefore, it has been slammed for its inherent static nature (Emery & Cogger, 1982 ; Habib, 2022 ; Habib & Kayani, 2022 ; Habib & Mourad, 2022 ). Alternatively, Richards and Laughlin ( 1980 ) proposed the adoption of cash conversion cycle (CCC), but this was slammed for being mathematically inaccurate, not focusing on funds tied up, and lacking differentiation in the weights appointed to each element of working capital.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To address these issues with traditional ratios, investigators have adopted alternative techniques for assessing WCME. DEA is one such measure that prior studies have relied on for assessing the WCME (Goel & Sharma, 2015 , 2016 ; Habib, 2022 ; Habib & Kayani, 2022 ; Habib & Mourad, 2022 ; Seth, Chadha, Ruparel, et al, 2020 ; Seth et al, 2021a , b ). A study of Indian companies from 2004 to 2013 reported a continual improvement in WCME and pointed out that the DEA technique was useful in overcoming the limitations associated with traditional measures of WCME (Goel & Sharma, 2015 , 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Efficiency scores can be mathematically described using the DEA approach, as follows (32,(49)(50)(51):…”
Section: Methodology Dea-malmquist Modelmentioning
confidence: 99%